Hubungan perapatan ibubapa rakan sebaya,penghargaan kendiri dan interaksi guru dengan persepsi tingkah laku buang bayi di kalangan pelajar sekolah menengah: satu kajian multietnik Sabah - Balan Rathakrishnan; Murnizam Hj Halik; Rosnah Ismail; Balakrishnan Parasuraman; Joki Perdani Sawai (Universiti Malaysia Sabah, 2011)
The study aims to examine the relationship between parent attachment, peer attachment, selfesteem and teacher interaction with perception on baby dumping behavior among multi-ethnic secondary school students in Sabah. A total of 781 middle school students from diverse ethnic groups have taken part in this survey. This survey study conducted by questionnaires, Inventory of Parent and Peer Attachment-Revised (IPPA-R) to measure parent and peer attachment, Rosenberg of Self-Esteem Scale (RSE) to measure self-esteem, School Attachment Questionnaire (SAQ) to measure teacher interaction, and perception on baby dumping behavior questionnaire to measure the dependent variable. Results showed that self-esteem correlates with perception on baby dumping behavior. In fact, the results also showed parent attachment, peer attachment and teacher interaction are not correlated with perception on baby dumping behavior among secondary school students from various ethnic groups in Sabah. Besides, there was no significant difference in the perception on baby dumping behavior among ethnic group students. implications of the study were discussed.